Cognitive and Brain Plasticity Induced by Physical Exercise, Cognitive Training, Video Games and Combined Interventions - Claudia Voelcker-Rehage (Frontiers Research Topics, 2018)
The premise of neuroplasticity on enhancing cognitive functioning among healthy as well as cognitively impaired individuals across the lifespan, and the potential of harnessing these processes to prevent cognitive decline attract substantial scientific and public interest. Indeed, the systematic evidence base for cognitive training, video games, physical exercise and other forms of brain stimulation such as entrain brain activity is growing rapidly. This Research Topic (RT) focused on recent research conducted in the field of cognitive and brain plasticity induced by physical activity, different types of cognitive training, including computerized interventions, learning therapy, video games, and combined intervention approaches as well as other forms of brain stimulation that target brain activity, including electroencephalography and neurofeedback. It contains 49 contributions to the topic, including Original Research articles (37), Clinical Trials (2), Reviews (5), Mini Reviews (2), Hypothesis and Theory (1), and Corrections (2).